Nurse records of comparative study between Mobile X-ray Outside the Hospital vs. X-ray at the Hospital Challenges Exposed - Hussain Saleh Mohammed Alyami, YOUSSEF SALEH HUSSAIN Zubayd, Salem masoud falah zubayd , Hussain masoud falah zubayd , Fayez Saleh Mohammed Alyami , Falah masoud falah zubayd , Ali Muhammad Saleh Zubaid , Salem hamad hassan alshariah (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Frail patients may benefit from receiving X-ray examinations at home to avoid the stress of hospital transport. This study investigated the impact of mobile X-ray on healthcare for such individuals ,with the primary outcome being the frequency of hospitalizations. Methods: Data were collected through questionnaires and Electronic Patient Records (EPR) from frail patients referred for mobile X-ray examinations in nursing homes and elderly care facilities. Mobile X-ray examinations were compared to hospital-based X-rays. Results: Analysis of data from 136 enrolled patients revealed no significant differences in hospitalizations or duration of hospital stays between mobile X-ray and hospital-based X-ray. Challenges encountered during the study included reluctance from doctors to refer patients for hospital-based X-rays and concerns from nursing home staff regarding patient frailty during post-X-ray questioning. Adjustments were made to the randomization method to address bias in initial data collection. Conclusions: While mobile X-ray did not significantly reduce hospitalizations compared to hospital-based X-ray in this exploratory study, it remains a valuable diagnostic tool for precise treatment in cases where hospital transportation is burdensome. Further research focusing on this aspect and conducting RCT studies in populations where mobile X-ray has not been previously explored is recommended.